Peran Audit Terhadap Akuntabilitas dan Transparansi Penggunaan Dana Bantuan Operasional Sekolah (BOS) pada Instansi Pendidikan - Berliani, Dedek; Noviyanti; Keristanti, Ruri; Juliani, Wahyuni; Dongoran, Faisal R (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The quality of primary and secondary education in Indonesia remains relatively low due to minimal service standards and widespread corruption in the education sector. To improve school quality, regular evaluation programs such as audits are necessary. Therefore, the objective of this literature review is to understand the role of audits in enhancing accountability and transparency in the use of BOS funds in educational institutions. This research method employs a systematic literature review using the PRISMA technique, focusing on research articles published from 2014 to 2024, totaling 8 articles. Based on the literature review, it is concluded that audits implemented to promote accountability and transparency have a positive impact on the management of BOS funds. Factors supporting the role of audits in accountability and transparency include: (1) stakeholder participation in BOS fund management, and (2) clarity of regulations in BOS fund management. Conversely, factors hindering this role include lack of human resource competence and insufficient media coverage. Therefore, it is hoped that these audits will enhance service quality in educational institutions through improved accountability and transparency in BOS fund management.